Social and Health Characteristics of Children with Disabilities and their Awareness of Helplines in the UAE Society - Alketbi, Bakhita; AlGharaibeh, Fakir (Al-Adab Journal, 2025)
The current study focused on the characteristics of children with disabilities in the United Arab Emirates community. In order to achieve the goals of the study, the descriptive analytical approach based on the study and analysis of all variables related to the problem in terms of the factors and reasons specified for it were used. Where a questionnaire consisting of two parts was applied: a section on family abuse of various forms (scenes violence, psychological abuse, physical abuse, abuse and neglect), and a section for awareness of the aid lines in the Emirates community. The questionnaire was used as a tool for study through a random sample that included 132 individuals, focusing on children with special needs, parents, home care providers and service provision centers for people with special needs. From the various centers of service provision in the UAE, including the Sharjah Humanitarian City, Al Ain Center for the Care and Rehabilitation of Disabled, the Zayed Upper Foundation for People of Determination, Al -Firdous Center for Rehabilitation of People with disabilities in Ajman. The results of the study found that the decrease in all types of abuse to which people with disabilities are exposed and the study found that the highest percentage of people with disabilities who were included in this study were those who have autism by 37.1%, then intellectual disability and then visual, and most of the disabilities were since birth and the results of the study showed that children have awareness of helplines if they need them.